Cover Image, Volume 56, Issue 1. (9th January 2018) - Denys, Gaël P. J.; Persat, Henri; Dettai, Agnès; Geiger, Matthias F.; Freyhof, Jörg; Fesquet, Justine; Keith, Philippe
Abstract : The cover image, by Gaël P. J. Denys et al., is based on the Original Paper Genetic and morphological discrimination of three species of ninespined stickleback Pungitius spp. (Teleostei, Gasterosteidae) in France with the revalidation of Pungitius vulgaris (Mauduyt, 1848), DOI10.1111/jzs.12178 .